Maternal vitamin D status and infant anthropometry in a US multi-centre cohort study. (May 2015) - Eckhardt, Cara L.; Gernand, Alison D.; Roth, Daniel E.; Bodnar, Lisa M.
Abstract Background: Maternal vitamin D status in pregnancy is linked to foetal growth and may impact infant growth. Aim: This study examined the association between maternal vitamin D status and infant anthropometry. Subjects and methods: Data came from n = 2473 mother–child pairs from the 12-site US Collaborative Perinatal Project (1959–1965). Maternal serum 25-hydroxyvitamin D (25(OH)D) was measured at ≤ 26 weeks gestation. Multivariate-adjusted linear mixed models were used to relate maternal vitamin D status to infant z-scores for length (LAZ), head circumference (HCZ), weight (WAZ) and BMI (BMIZ), measured at birth and 4, 8 and 12 months. Results: Infants with maternal 25(OH)D ≥30 nmol/L vs <30 nmol/L had LAZ and HCZ measures 0.13 (95% CI = 0.03–0.23) and 0.20 (95% CI = 0.11–0.28) units higher, respectively, across the first year of life. Similar differences in WAZ and BMIZ at birth were resolved by 12 months of age due to interactions indicating steeper age slopes in infants with maternal 25(OH)D <30 nmol/L. Conclusion: Low maternal vitamin D status was associated with deficits at birth in infant weight and BMI that were recouped across the first year of life; associations with reduced measures of linear and skeletal growth were sustained from birth to 12 months.